Integration of STEAM in Solving Numerical Method Problems - Ari Indriani; Novi Mayasari; A. Kholiqul Amin; Da’imatun Nasichah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The learning model prepared for the 21st century is STEAM. In particular, the numerical method topic of the bisection method is taught using the STEAM learning model with the help of MS Excel. The problem in this study is whether the STEAM learning model can help students solve bisection method problems. The aim of this study is to determine whether the STEAM learning model can assist students in solving bisection method problems. This is a quantitative study with a population of all students taking the numerical methods course. The sample consists of semester 6 students from classes A and B, and the sampling technique used is saturated sampling. The prerequisite tests conducted are normality and homogeneity tests. The analysis technique used is the t-test, with the results showing t_calculated = 2.107 and t_table = 2.074. The null hypothesis (H0) is rejected, indicating that STEAM and conventional learning models have different effects. Furthermore, based on the average scores of both classes, the STEAM learning model has a more significant effect than the conventional method. In conclusion, the STEAM learning model with the help of MS Excel can assist students in solving numerical method problems.